Male deity identifiable as a dikapala on the eastern wall of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
On the right corner of the rear or eastern wall of the garbhagriha (sanctum sanctorum), there is another male deity identifiable as a dikapala (deity of the cardinal directions). The four-armed deity, like others, has been subject to damages, with his face entirely erased and three of his arms broken. The well-adorned dikapala is depicted holding a trishula (trident) in his upper right hand. Seated at the bottom is a bull, indicating that this figure may be Ishana, often portrayed holding a trishula with a bull as his vahana (mount).